WEED CONTROL EFFICACY OF TRIAFAMONE 200 SC IN TRANSPLANTED RICE - B, JYOTHI BASU (The Journal of Research ANGRAU, 2026)
A field investigation conducted during two consecutive cropping seasons (Rabi 2017–18 and Kharif 2018–19) at the Agricultural Research Station, Jangamaheswarapuram, Andhra Pradesh, India, to evaluate the performance of Triafamone 200 SC in transplanted Rice.”Among the various herbicide treatments, Triafamone 200 SC applied at 100 g a.i. ha-¹ at 0-3 days after transplanting (DAT) recorded superior weed suppression efficiency in Rabi 2017-18 (68.64%) and in Kharif 2018-19 (60.83%) and also yielded 4967 kg ha-1 in Rabi and 5518 kg ha-1 in Kharif,with performance comparable to conventional farmer-managed two hand weeding practices, which produced 5342 kg ha-1 in Rabi and 5849 kg ha-1 in Kharif. The weed-free treatment recorded the maximum yields (5762 kg ha-1 in Rabi and 6376 kg ha-1 in Kharif), while the weedy check plots showed the lowest yields (3066 kg ha-1 in Rabi and 3825 kg ha-1 in Kharif).